×

Applying blocking measures progressively to malicious network traffic

  • US 7,707,633 B2
  • Filed: 10/12/2007
  • Issued: 04/27/2010
  • Est. Priority Date: 05/20/2003
  • Status: Expired due to Fees
First Claim
Patent Images

1. A method of responding progressively to network anomalies, said method comprising:

  • applying a blocking measure or suspending the blocking measure in accordance with a state B(t) of the blocking measure at time t for discrete values of t which are integer multiples of a time interval Dt, said discrete values of t representing t=0, Dt, 2*Dt, . . . , J*Dt, wherein J is a positive integer equal to or greater than 2;

    wherein if B(t)=1 then the blocking measure is applied and if B(t)=0 then the blocking measure is suspended;

    wherein D(t)=1 if a last output measurement of a network anomaly detector indicates that a network anomaly is present and D(t)=0 otherwise;

    wherein S(t) is a time stamp indicating the absolute start time of a most recent sequence of time values with consecutive application of the blocking measure;

    wherein K(t) is a count of the number of times, within a present epoch of consecutive detections of network anomaly, that the blocking measure has been suspended and then re-applied in response to detection of a persistent network anomaly;

    wherein P(t) is a duration of the blocking measure and is a non-decreasing function of K(t);

    wherein a specified positive integer L is a maximum permitted value of K(t);

    wherein t=0 is a time prior to execution of a loop of J iterations denoted as iterations 1, 2, . . . , J;

    wherein at t=0, B(0)=1, A(0)=1, S(0)=0, K(0)=0, and P(0)=P0=I*Dt, wherein I is a positive integer;

    wherein B(t), S(t), and K(t) are iteratively computed during execution of the loop such that in each iteration;


    B(t+Dt)=D(t)*(1−

    B(t))+(1−

    D(t)*(1−

    B(t)))*if(t+Dt−

    S
    (t)<

    P(t) then 1, else

         0),
    S(t+Dt)=B(t+Dt)*(1−

    B(t))*(t+Dt−

    S
    (t))+S(t),
    K(t+Dt)=min{L, D(t)*(K(t)+B(t+Dt)*(1−

    B(t)+(1−

    D(t))*B(t+Dt)*(K(t)+1−

    B(t))))},
    t=t+DT after B(t+Dt), S(t+Dt), and K(t+Dt) have been determined.

View all claims
  • 0 Assignments
Timeline View
Assignment View
    ×
    ×